Some Introductory Words For Two Little Earth Cousins - David W Jardine (University of Calgary, 2014)
This article is an introduction to the subsequent one by Jodi Latremouille's "My Treasured Relation." It demonstrates that hermeneutic work is always about the application of particular cases to universals, demanding of universals to listen to the difference that the case portends.